Analytical Hierarchy Process (AHP) : A Strategy to develop Disaster Resilient Tourism Priority in Indonesia - Suriadi, Nur Adyla; Priadmodjo, Anggit; Gomes, Lucio Marcal; Nurlaela, Nurlaela; Tasrif, Ali Akbar (Journal of Applied Engineering and Technological Science (JAETS), 2025)
Majene Regency in Sulawesi Barat, Indonesia, ranks as one of the regions most susceptible to natural disasters, with its tourism sector highly exposed to these risks. Given that nearly all tourism destinations in the region lie within hazard-prone zones, the economic vulnerability of this sector is critical. This research aims to formulate a disaster-resilient tourism strategy for Majene by employing the Analytical Hierarchy Process (AHP), a decision-making framework that enables structured prioritization based on stakeholder input. The study involved twelve experts from government, academia, the private sector, and the local community who conducted pairwise comparisons of five strategic categories derived from the World Bank’s disaster-resilient tourism framework: understanding risk, planning and prioritization, mitigation and preparedness, response and recovery, and long-term resilience actions. The results revealed that long-term resilience actions (22.7%), understanding risk (22.3%), and mitigation and preparedness (21.4%) were the top priorities. Key programs within these strategies include integrating tourism into national risk assessments, embedding tourism into disaster management planning, and establishing early warning systems. These findings offer actionable insights for local governments and tourism planners, highlighting strategic priorities that can guide policy development and foster sustainable, disaster-resilient tourism in vulnerable areas like Majene.